Africa Fertilizer and Soil Health Action Plan: Outcome 4 - African Union Development Agency- NEPAD (2024)
This poster presents Outcome 4 - ‘Institutional and Human Capacity Enhanced for Sustainable Soil Health and Fertilizer Management’ of the Africa Fertilizer and Soil Health (AFSH) Action Plan. It gives the AFSH Action Plan’s Vision, Expected Impact, Strategy and the contributing Outcome 4 with associated Outputs (4.1 to 4.4) and Action areas.